Effect of lanthanum addition on microstructure and hardness as cooling rate function of ADC12 eutectic cast alloy - Ahmad, Rosli (2015)

(untitled)
This paper presents the experimental investigation conducted on ADC12 cast alloy. The main objective of the research is to investigate the effect of 1.5%La addition with different cooling rate on microstructure and hardness value of ADC12 cast alloy. The Ceramic Mold with different thickness dimensions was use to obtained different cooling rate. The Si structure became modified by increase the cooling rate of base alloy. With La addition the Si size observed smaller area than base alloy when the cooling rate increases. In addition, the higher cooling rate and La addition improves the hardness specially at lower thickness with La addition